ANALISIS EFEKTIVITAS DAN KONTRIBUSI BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN TERHADAP PENDAPATAN ASLI DAERAH DI KABUPATEN NAGEKEO - Rua, Skolastika Febronia Menge; De Rozari, Petrus Emanuel; Tameno, Nikson (LPPM University 17 Agustus 1945 Samarinda, 2023)
This study aims to determine whether the collection of Fees for Acquisition of Rights on Land and Buildings (BPHTB) is effective and contributes to Local Original Revenue and Local Taxes of Nagekeo Regency, especially from 2017 to 2021 by analyzing these two variables and the causes of the decline in BPHTB targets, especially from 2019 to 2020. This type of study is a combination research method (Mix Methods) with a Sequential Explanatory model conducted through a case study. Data collection techniques using documentation and interviews. The result of this study is the level of effectiveness of the Fees for Acquisition of Rights on Land and Buildings (BPHTB) during 2017-2021 has an average effectiveness value of 120.71% which is considered very effective. In 2019-2020 the effectiveness criteria dropped to be quite effective because it was achieved less than 90%. The contribution of the Fees for Acquisition of Rights on Land and Buildings (BPHTB) to the Local Original Revenue (PAD) of Nagekeo Regency during 2017-2021 has an average contribution of 0.40% which in the calculation is interpreted as